Pathogenetic Rationale for the Use of Probiotics in Antibiotic-Associated Diarrhea in Children - O.Ye. Chernysheva (Zaslavsky O.Yu., 2015)
The article deals with the topical issues of irrational administration of antibiotics in children, development of abnormal side effects and complications, in particular antibiotic-associated diarrhea. The modern means for the prevention and treatment of this group of diseases, in particular the use of probiotics, are presented.